Evolving therapeutics in colorectal cancer peritoneal metastases - Justin M. Bader; Nicole Aguirre; Kurt S. Schultz; Kwasi Ansere Ofori; Elizabeth Godfrey; Princy Gupta; Robert Tseng; Michael Cecchini; Raghav Sundar; Kiran Turaga (Cancer and Metastasis Reviews, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

ELIME-IMS hybrid assay for Salmonella detection in swine mesenteric lymph nodes at slaughterhouse - M. Trevisani; M. Conter; M. Cecchini; L. Lamperti; L. Andriani; M. Rega; C. Bacci; M. Perri; S. Bonardi (Food Microbiology, 2025)

Linking conventional activated sludge treatment plant performances for micropollutants removal to environmental risk and SimpleTreat model assessment - C. Di Marcantonio; A. Chiavola; D. Spagnoli; B. Meşe; F. Margarita; V. Gioia; A. Frugis; S. Leoni; G. Cecchini; M. Spizzirri; M. R. Boni (International Journal of Environmental Science and Technology, 2024)
The attention to the contaminants of emerging concerns or micropollutants is continuously rising, also stimulated by the new initiatives at European level. The present study focuses on the removal of target micropollutants in a conventional activated sludge wastewater treatment plant which is the most common system and considered a source of micropollutants to the environment. The aims were to evaluate the removal efficiency of different stages of the wastewater treatment plant and to conduct the Environmental Risk Assessment on the final effluent. As indicated by the European’s guidelines on Environmental Risk Assessment, the SimpleTreat4.1 model was applied to this purpose: different values of the biodegradation constant, which represents the key factor for modelling, were applied, and the effects on the quality of prediction were evaluated. The evaluations were carried out thorough 3-year monitoring activity in a full-scale wastewater treatment plant on 10 micropollutants belonging to the classes of illicit drugs, pharmaceuticals and psychoactive. The model was found statistically not satisfactory for most of the investigated micropollutants. A better prediction was obtained when the biodegradation constant was calculated based on the full-scale data. Nonetheless, the results obtained in terms of risk were considered acceptable and comparable among each other. Graphical abstract

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Bio-based production of medium-chain carboxylic acids from food waste and sludge without chemical addition: The pivotal role of mix ratio and pretreatment - Barbara Tonanzi; Agata Gallipoli; Alessandro Frugis; Andrea Gianico; Marco Lazzazzara; Stefania Angelini; Giancarlo Cecchini; Camilla M. Braguglia (Journal of Cleaner Production, 2024)

Correction to: Relative Importance of Climate, Soil and Plant Functional Traits During the Early Decomposition Stage of Standardized Litter - Nicolas Fanin; Sophie Bezaud; Judith M. Sarneel; Sébastien Cecchini; Manuel Nicolas; Laurent Augusto (Ecosystems, 2021)

Relative Importance of Climate, Soil and Plant Functional Traits During the Early Decomposition Stage of Standardized Litter - Nicolas Fanin; Sophie Bezaud; Judith M. Sarneel; Sébastien Cecchini; Manuel Nicolas; Laurent Augusto (Ecosystems, 2020)

The response of soil solution chemistry in European forests to decreasing acid deposition - James Johnson; Elisabeth Graf Pannatier; Stefano Carnicelli; Guia Cecchini; Nicholas Clarke; Nathalie Cools; Karin Hansen; Henning Meesenburg; Tiina M. Nieminen; Gunilla Pihl‐Karlsson; Hugues Titeux; Elena Vanguelova; et al. (Global Change Biology, 2018)
Acid deposition arising from sulphur (S) and nitrogen (N) emissions from fossil fuel combustion and agriculture has contributed to the acidification of terrestrial ecosystems in many regions globally. However, in Europe and North America, S deposition has greatly decreased in recent decades due to emissions controls. In this study, we assessed the response of soil solution chemistry in mineral horizons of European forests to these changes. Trends in pH , acid neutralizing capacity ( ANC ), major ions, total aluminium (Al tot ) and dissolved organic carbon were determined for the period 1995–2012. Plots with at least 10 years of observations from the ICP Forests monitoring network were used. Trends were assessed for the upper mineral soil (10–20 cm, 104 plots) and subsoil (40–80 cm, 162 plots). There was a large decrease in the concentration of sulphate ( ) in soil solution; over a 10‐year period (2000–2010), decreased by 52% at 10–20 cm and 40% at 40–80 cm. Nitrate was unchanged at 10–20 cm but decreased at 40–80 cm. The decrease in acid anions was accompanied by a large and significant decrease in the concentration of the nutrient base cations: calcium, magnesium and potassium (Bc = Ca 2+ + Mg 2+ + K + ) and Al tot over the entire dataset. The response of soil solution acidity was nonuniform. At 10–20 cm, ANC increased in acid‐sensitive soils (base saturation ≤10%) indicating a recovery, but ANC decreased in soils with base saturation >10%. At 40–80 cm, ANC remained unchanged in acid‐sensitive soils (base saturation ≤20%, ≤ 4.5) and decreased in better‐buffered soils (base saturation >20%, > 4.5). In addition, the molar ratio of Bc to Al tot either did not change or decreased. The results suggest a long‐time lag between emission abatement and changes in soil solution acidity and underline the importance of long‐term monitoring in evaluating ecosystem response to decreases in deposition.

Phenolics and antioxidant activity in different cultivars/clones of Vitis vinifera L. seeds over two years - B. Giannini; N. Mulinacci; G. Pasqua; M. Innocenti; A. Valletta; F. Cecchini (Plant Biosystems, 2016)

Quantification of lead and cadmium in poultry and bird game meat by square-wave anodic-stripping voltammetry - M. Trevisani; M. Cecchini; L. Taffetani; L. Vercellotti; R. Rosmini (Food Additives & Contaminants: Part A, 2011)

Early genomic responses to salicylic acid in Arabidopsis - Francisca Blanco; Paula Salinas; Nicolás M. Cecchini; Xavier Jordana; Paul Van Hummelen; María Elena Alvarez; Loreto Holuigue (Plant Molecular Biology, 2009)

Variation in fructooligosaccharide contents during plant development and in different cultivars of durum wheat - A. Paradiso; C. Cecchini; E. Greco; M. G. D'Egidio; L. De Gara (Plant Biosystems, 2008)

Two genetically related strains of Tuber borchii produce Tilia mycorrhizas with different morphological traits - D. Sisti; G. Giomaro; M. Cecchini; A. Faccio; M. Novero; P. Bonfante (Mycorrhiza, 2003)

Anatomical and morphological characterization of mycorrhizas of five strains of Tuber borchii Vittad - G. Giomaro; A. Zambonelli; D. Sisti; M. Cecchini; V. Evangelista; V. Stocchi (Mycorrhiza, 2000)

Influence of environmental temperature and water oxygen concentration on gas diffusion distance in sea bass (Dicentrarchus labrax, L.) - M. Saroglia; S. Cecchini; G. Terova; A. Caputo; A. De Stradis (Fish Physiology and Biochemistry, 2000)

Ascorbate dynamics in embryos and larvae of sea bass and sea bream, originating from broodstocks fed supplements of ascorbic acid - G. Terova; M. Saroglia; Z. Gy. Papp; S. Cecchini (Aquaculture International, 1998)

Force responses to fast ramp stretches in stimulated frog skeletal muscle fibres - M. A. Bagni; G. Cecchi; E. Cecchini; B. Colombini; F. Colomo (Journal of Muscle Research and Cell Motility, 1998)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Baroreceptor responses derived from a fundamental concept - Mona F. Taher; Albert B. P. Cecchini; Mark A. Allen; Sherif R. Gobran; Robert C. Gorman; Brian L. Guthrie; Kyle A. Lingenfelter; Sina Y. Rabbany; Philip M. Rolchigo; Julius Melbin; Abraham Noordergraaf (Annals of Biomedical Engineering, 1988)